Recycling of waste material through bio-decomposer and their impact on succeeding crop - Singh, R K; Sharma, D P; Singh, S R K (Indian Farming, 2022)
A large portion of the residues is burnt on-farm primarily to clear the field for sowing of the succeeding crop. Because crop residues interfere with tillage and seeding operations for the next crop, farmers often prefer to burn the residue in situ. Burning of crop residues is intensifying problems in recent years due to shortage of human labour, high cost of removing the crop residues by conventional methods and use of combines for harvesting of crops. In this situation use of biodecomposer for fast decomposition of crop residue or livestock waste materials will be very helpful. Bio-decomposer consortium producing digestive enzymes that they release into their surroundings helps in decomposition of residue. They absorb the breakdown products and release nutrient ions for plant uptake in the process. This activity is important for carbon and nutrient cycling through recycling of waste material by the use of available resource to enhance the production and productivity of crops and also reduces the cost of cultivation and environmental pollution.